Model Kooperatif Team Games Tournament (TGT): Peningkatan kreatifitas, kerjasama dan keterampilan bermain sepakbola siswa tunarungu - Sembiring, Ibastanta; Tarigan, Beltasar; Budiana, Dian (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
The purpose of this study was to determine and examine the effect of the Team Games Tournament (TGT) learning model on increasing creativity, cooperation, soccer skills in deaf students. The method used was an experimental method with a research design was a pretest and posttest design. The population in this study were students of SLB Negeri Cicendo and the sample was 20 grade students. The sampling technique is total sampling. The research instrument is creativity developed from Juliantine's research (2010) and the instrument for playing football skills using GPAI (Game Performance Assessment Instrument Components). The results showed that: (1) there was an effect of the Team Games Tournament (TGT) type of cooperative learning model on creativity in deaf students, (2) there was an influence of the Team Games Tournament (TGT) type of cooperative learning model on cooperation among deaf students, (3) There is the influence of the Team Games Tournament (TGT) type of cooperative learning model on the skills of playing football in deaf students, (4) there are differences in the Team Games Tournament (TGT) type of cooperative learning model and the conventional learning model on creativity, cooperation, and football playing skills of deaf students . Referring to the results of the analysis and research conclusions, the authors provide several recommendations for other researchers who are interested in answering new findings, namely regarding the absence of influence on the variables of creativity, cooperation, football skills through the Team Games Tournament learning model. This may be a weakness in the researcher regarding the research method, data collection techniques, and the sample involved.